Perlindungan Konsumen Terhadap Kerugian Akibat Skimming dan Kebocoran Data di Bank - Ria Yusnita; Lydia Aprilia Pritiwi; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2025)
This research analyzes how Indonesian consumers are protected from financial losses due to cybercrimes like card data theft (skimming) and personal information breaches within the banking sector. Given the rise of such incidents, we examine the relevant legal framework, specifically the Consumer Protection Law and OJK (Financial Services Authority) regulations, to understand their effectiveness in safeguarding customers. The primary focus of this study is to investigate exoneration clauses often found in agreements between banks and customers, which potentially limit the bank's liability when these incidents occur. Using a normative approach, we also identify existing dispute resolution processes and various challenges consumers face when filing claims. We anticipate that the findings of this study will yield concrete recommendations to strengthen regulations, enhance bank operational transparency, and educate consumers, ultimately contributing to a safer and fairer banking system.